An efficient channelization architecture and its implementation for radio astronomy. (16th August 2021) - Liu, W.; Meng, Q.; Wang, C.; Zhou, C.; Yao, S.; Tariq, I.
Abstract: Channelization is one of the most important parts in a Digital Back-End(DBE) for radio astronomy. A DBE with wider bandwidth and higher resolution consumes larger amount of computing and memory resources, which results in much higher hardware cost. This paper presents an efficient channelization architecture, which consists of Bit-Inverted, Parallel Complex Fast Fourier Transform(BIPC-FFT) and In-place Forward-Backward Decomposition(IPFBD). The efficient architecture can assist with saving a lot of resources, so a wide-band and high-resolution DBE can be implemented on an resource restricted platform. Based on the efficient channelization architecture, we designed a Dual-Input, 64K-Channelized prototype DBE with 1.2 GHz bandwidth on a Xilinx Virtex-6 LX240T Field Programmable Gate Array(FPGA) chip. The test results in the lab and observation results at Yunnan Observatory demonstrate the DBE can be used for radio astronomy.